Harnessing electrochemical pH gradient for direct air capture with hydrogen and oxygen by-products in a calcium-based loop. Issue 17 (1st August 2021) - Zhou, Congquan; Ni, Jihong; Chen, Huiqi; Guan, Xiaofei
Abstract : A large pH gradient generated electrochemically in a neutral water electrolysis cell is harnessed for direct air capture (DAC) in addition to simultaneous production of CO2, O2 and H2 in separate chambers. Abstract : Direct air capture is considered as one of the most important strategies for controlling the CO2 concentration in the earth's atmosphere and thereby mitigating climate change. The current direct air capture technologies still suffer from various issues, such as high energy cost or material instability, which may limit their large-scale applications. Here, we report two new processes that harness electrochemical pH gradient for direct air capture with a calcium-based loop. The first process involves CaCO3 dissolution and Ca(OH)2 generation in a water electrolysis cell followed by CO2 absorption in a Ca(OH)2 –NaOH slurry, regenerating CaCO3 and closing the loop. NaOH is identified to be an effective catalyst for CO2 fixation in the form of CaCO3 . The second process enables simultaneous CO2 capture and carbonate regeneration. Both processes eliminate high-temperature CaCO3 calcination, and thereby reduce the energy use and emissions. The valuable H2 and O2 by-products have various applications. The calcium-based loop that harnesses electrochemical pH gradient represents a promising approach for direct air capture in an economical and environmentally friendly way.